URGENSI PENDIDIKAN TEKNOHUMASITIK CORE ETHICAL VALUES (PERSPEKTIF CHARACTER BUILDING) - I Made Ariasa Giri (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
Education is a crucial urgency strategically in preserving the value character systemthat develops in life. Character is the unity between mindset (logos), conscience (ethos), andattitude (patos). Character is the values of human behavior that relate to God, humans,environment, nationality and itself which is reflected in the thoughts, attitudes, feelings, words,deeds based on religious, legal, karmic rules, culture and customs. Strengthening moral education(moral education) or character education in the current context is very relevant to overcomethe moral crisis that is engulfing this nation. Therefore, technohumanistic education shoulddevelop and make activities the basis of education itself. Technicumanistic character andeducation must be comprehensively defined, including thoughts, feelings, and behavior. In thecharacter education program as the core of technohumanistic education which generally touchesthe cognitive, affective, psychomotor and metacognitive domains contains broader meanings,and ultimately can involve aspects of behavior in moral life. Technohumanistic education basedon the mastery of science and technology based on a solid foundation of understanding, concernabout basic ethical values, and actions based on core ethical values should be highlightedthrough a moral lens and see how things really are which affects the values in the school andthe character of the students.Keywords: Technical Technology Education, Core Ethical Values, Character Building